PENGARUH KOMUNIKASI INTERPERSONAL ANTAR PEGAWAI TERHADAP KINERJA PEGAWAI DINAS PARIWISATA, KEBUDAYAAN, PEMUDA DAN OLAHRAGA KABUPATEN MAGETAN - Pramono, Kurniawan (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2017)
Dinas Pariwisata, Kebudayaan, Pemuda dan Olah Raga (DISPARBUDPORA) Magetan Regency as an institution that regulates all matters relating to tourism in Magetan regency is actively carry out development in the tourism sector in order to boost the conservation of tourism objects, empower the potential around the tourism object and conduct promotions to optimize the tourism sector in attracting investors as well as attracting more visitors. The purpose of this research is to find out the correlation between interpersonal communication that happened to Dinas Pariwisata, Kebudayaan, Pemuda dan Olah Raga of Magetan with performance of employee. Methods in this study using quantitative methods by distributing questionnaires to employees of the Dinas Pariwisata, Kebudayaan, Pemuda dan Olah Raga, with the results of research that together interpersonal communication between employees have a significant effect on employee performance on the Department of Tourism, Culture, Youth and Magetan Regency Sport with F count of 5,808 and significance 0.01, where the significance value 0.01 <0.05, it is concluded that the dependentvariable influence simultaneously to independent variable, and interpersonal communication between employee and employee performance have partially positive effect.